2005
DOI: 10.1093/heapro/dai017
|View full text |Cite
|
Sign up to set email alerts
|

Welfare babies: poor children's experiences informing healthy peer relationships in Canada

Abstract: Positive peer relationships among children living in poverty are important for their well-being, resiliency and mental and physical health. This paper explicates the 'felt experience' of children living in poverty, and the implications of these experiences for healthy peer relationships, from a re-analysis of two qualitative research studies in Canada examining children living in food insecure circumstances. Poor children feel deprived, part of the 'poor group', embarrassed, hurt, picked on, inadequate and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(41 reference statements)
0
12
0
1
Order By: Relevance
“…However, research by Vaughn et al (2000) and Vaughn, Colvin, Azria, Caya, and Krzysik (2001) suggested that patterns of friendship in preschool children from low-income ethnic minority backgrounds are similar to patterns reported in more economically advantaged groups from majority ethnic backgrounds. Moreover, Robinson, McIntyre, and Officer (2005) highlighted the importance of positive peer relationships for the well-being, resiliency, and mental and physical health of children living in poverty. Less research has been done on peer relationships in groups of children who are immigrants, and the authors could find no studies that included a sample of preschool children.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, research by Vaughn et al (2000) and Vaughn, Colvin, Azria, Caya, and Krzysik (2001) suggested that patterns of friendship in preschool children from low-income ethnic minority backgrounds are similar to patterns reported in more economically advantaged groups from majority ethnic backgrounds. Moreover, Robinson, McIntyre, and Officer (2005) highlighted the importance of positive peer relationships for the well-being, resiliency, and mental and physical health of children living in poverty. Less research has been done on peer relationships in groups of children who are immigrants, and the authors could find no studies that included a sample of preschool children.…”
Section: The Present Studymentioning
confidence: 99%
“…Moreover, given the sample employed in this study, this practical implication may be especially important for government preschool initiatives tackling social disadvantage (such as Early Start, Head Start, and Sure Start). The facilitation of friendship maintenance across this transition may be particularly beneficial for this sample considering the hypothesized protective influence of positive peer relationships for the well-being, resiliency, and mental and physical health of children living in poverty (Robinson et al, 2005).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This focus on moral experiences can also help advance our understanding of these children as active moral agents. One study documented the impact of poverty on children's social status, which is linked to feeling deprived, feeling excluded from peers (e.g., receiving labels such as "welfare babies"), having low self-esteem, or feeling responsible for improving their financial situation (Robinson et al, 2005). Very little information related to their experience is available.…”
Section: Exploring the Moral Experiences Of Children Living In Povertymentioning
confidence: 99%
“…The basic factors responsible for the occurrence of health inequalities are of a social and economic nature and include: level of education, income and employment. Poverty, being one of the main causes of inequalities, has an impact on reducing the chances of personal, social and emotional development, as well as quality of young people's future lives [4]. According to statistical data, in 2010, approximately 12% of children and teenagers lived below the relative poverty threshold and over 8% lived below the absolute poverty threshold [5].…”
Section: Introductionmentioning
confidence: 99%